Platelet-to-lymphocyte ratio (PLR) and Plateletcrit (PCT) in young patients with morbid obesity - Erdal,Emrah (2019)
SUMMARY OBJECTIVE To compare the complete blood counts, namely the plateletcrit (PCT) and Platelet-To-Lymphocyte Ratio (PLR) of healthy subjects and those with morbid obesity in the young population. METHODS We included 45 patients with morbid obesity (body mass index -BMI - greater than or equal to 45 kg/m2) and 45 healthy subjects (BMI less than or equal to 25 kg/m2) in our study. Blood samples were obtained from the participants following a 12-hour fasting period. Then we evaluated the levels of hemoglobin (Hb), hematocrit (HCT), red cell distribution width (RDW), mean platelet volume (MPV), white blood cell (WBC), PLR, platelet counts, and PCT in the complete blood count. RESULTS The morbid obesity group had significantly higher platelet counts and PCT values (p<0.001), and PLR values (p=0.033). The value of WBC was also higher in the obese group (p=0.001). MPV was lower in the obesity group but not statistically significant (p=0.815). No significant difference was found between hemoglobin and hematocrit values in these groups; but RDW valuewere higher and statistically significant in the obese group (p=0.001). CONCLUSION PLR or PCT may be more useful as a marker in determining an increased thrombotic state and inflammatory response in morbid obesity.